Audiomotor Temporal Recalibration Modulates Decision Criterion of Self-Agency but Not Perceptual Sensitivity - Sugano, Yoshimori (Frontiers in Psychology, 2021)
Exposure to delayed sensory feedback changes perceived simultaneity between action and feedback (temporal recalibration: TR) and even modulates the sense of agency (SoA) over the feedback. To date, however, it is not clear whether the modulation of SoA by TR is caused by a change in perceptual sensitivity or decision criterion of self-agency. This experimental research aimed to tease apart these two by applying the signal detection theory (SDT) to the agency judgment over auditory feedback after voluntary action. Participants heard a short sequence of tone pips with equal inter-onset intervals, and they reproduced it by pressing a computer mouse. The delay of each tone pip after the mouse-press was manipulated as 80 ms (baseline) or 180 ms (delayed). Subsequently, the participants reproduced it again, in which the delay was fixed at 80 ms and there was a 50% chance that the computer took over the control of the tone pips from the participants. The participants’ task was to discriminate who controlled the tone pips and to judge synchrony between tone pips and mouse-presses. Results showed that the modulation of the SoA by the TR is caused by a shift in the decision criterion, but not in the perceptual sensitivity of agency.